Perkembangan Tari Tauh Di Desa Rantau Pandan Kecamatan Rantau Pandan Kabupaten Bungo - Vera Megasari; Darmawati Darmawati (SENDRATASIK UNP, 2020)
This research aims to reveal, describe, and analyze the development of Tauh Dance in Rantau Pandan Village, Rantau Pandan District, Bungo Regency, Jambi Province. This research used a descriptive analysis method. The object of this research was Tauh dance in Rantau Pandan District, Bungo Regency, Jambi Province. The data used in this study were primary and secondary data. The main instrument was the researcher itself. The data were collected through literature study, observation, interview, and documentation. The data analysis was conducted by using interpretation technique so that the truth can be obtained. The results show that Tauh Dance in Rantau Pandan Village has developed into a new form that can be seen through the processing of motion, clothing, make-up, property, time and place of performance as well as aspects of dancers packaged in new forms. In motion, there is a development in terms of movement assertiveness and motion motives. In costumes, there is a development in terms of uniformity, similarity between dancers, and harmony in choosing colors for male and female dancers’ costumes. Thus, the process of developing Tauh dance in Rantau Pandan District is supported because there is a desire from Alsobri to keep Tauh dance by turning it into an attractive Tauh dance for Rantau Pandan community as well as maintaining cultural heritage and forming the identity of the local Village.